The effect of positive inter-group contact on cooperation: the moderating role of individualism - Xiao, Rikui; Li, Shuxin (Frontiers in Psychology, 2024)
Introduction The effect of intergroup contact on cooperation is well documented, but little is known about the cultural moderators of this relationship. Contributing to the literature, we examined whether cultural orientation moderates the effect of positive intergroup contact on cooperation and places emphasis on individualism. Methods By creating a gamecooperation situation by the trust game paradigm, 322 Taiwanese youth were involved in the study and completed the positive intergroup contact scale, individual-collectivism scale, and social distance scale. Results (1) positive intergroup contact effectively promotes cooperative behavior; (2) Taiwanese youth who have closer social distance with mainland youth demonstrate higher levels of cooperative behavior after group interactions than larger social distance; and (3) individualism has a significant moderating role in the relationship between positive inter-group contact and cooperation. The effect of positive inter-group contact on cooperation became stronger in the less individualistic group. The effect of social distance on cooperation became stronger in the less individualistic group.Cultural orientation represented by individualism is proved to be one moderato of the intergroup contact-cooperation relationship.